The Influence of Calcium Chloride on the Setting Time, Solubility, Disintegration, and pH of Mineral Trioxide Aggregate and White Portland Cement with a Radiopacifier - Bortoluzzi, Eduardo Antunes; Broon, Norberto Juarez; Bramante, Clovis Monteiro; Felippe, Wilson Tadeu; Tanomaru Filho, Mario [UNESP]; Esberard, Roberto Miranda [UNESP] (Elsevier B.V., 2009)
This study evaluated the influence of addition of 10% calcium chloride (CaCl(2)) on the setting time, solubility, disintegration, and pH of white MTA (WMTA) and white Portland cement (WPC). A test of the setting time was performed following the #57 ADA specifications and a test of the final setting time according to the ASTM. For the solubility tests disintegration and pH, Teflon rings were filled with the cements and weighed after setting. After 24 h in a desiccator, they were once again weighed. Thereafter, they were immersed in MiliQ water for 24 and 72 h and 7, 14, and 28 days, with maintenance in the desiccator and weighing between periods. The pH of water in which the rings were immersed was measured immediately after contact with them and in the other periods. The addition of CaCl(2) provided a significant reduction (50%) in the initial setting time of cements. The final setting time of WMTA was reduced in 35.5% and the final setting time of WPC in 68.5%. The WMTA with CaCl(2) absorbed water and gained weight with time, except for in the 24-h period. The addition of CaCl(2) to the WPC reduced its solubility. The addition of CaCl(2) increased the pH of WMTA in the immediate period and at 24 and 72 h and for WPC in the immediate period and at 24 h. The addition of CaCl(2) to WMTA and WPC reduced the setting times and solubility of both and increased the pH of cements in the initial periods. (J Endod 2009;35:550-554)
Keywords: Calcium chloride; mineral trioxide aggregate; Portland cement